Sound American: The Occam Ocean Issue No. 26 - Wooley, Nate 1974- (New York Anthology of Recorded Music, 2021)
Dedicated to Éliane Radigue’s radical musical ecosystem, OCCAM Ocean, and includes exclusive interviews with Radigue's collaborators and interpreters, including: Charles Curtis, Carol Robinson, Rhodri Davies, Catherine Lamb, Julia Eckhardt, Silvia Tarozzi, Dafne Vicente-Sandoval, Laetitia Sonami, and Frédéric Blondy. inti figgis-vizueta contributes a composition to the ongoing Exquisite Corpse series.⁣⁣ The issue also includes an exclusive poster designed by Remake Design that documents and graphically interprets Radigue's compositional system, connections, and collaborators.⁣⁣
Keywords: Radigue, Éliane; Composing; Esthetics; Chamber music